(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Due to the increase in population the water usage is increased which directly effects on waste water generation in huge manner. It is very important nowadays to treat such waste water for its reuse and to treat it before discharging into the local bodies such as lake, river, ponds etc. Hence, there is need arises to treat the waste water before discharging it into the environment. Methods for the treatment of waste water are Activated Sludge Process, Trickling Filter, Extended Aeration Sludge Process, Aerated Lagoon, Oxidation Ditch, Waste Stabilization Pond, Up-flow Anaerobic Sludge Blanket, Membrane BioReactor, Moving Bed Bio-film reactor, Sequential Batch reactor and Rotating Biological Contact-discs. In this paper, comparative study between Activated sludge process and Stabilization pond has been carried out to reduce the BOD value.